The dilemma between fertility and work: How did the Universal Two-Child policy affect Chinese women's labor income? - Yi Chen; Zu Wang (PLoS ONE)
Based on China Family Panel Studies (CFPS) data from 2012 to 2020, we estimate the effect of the "Universal Two-Child" (UTC) policy on women's employment income in China by the Difference-in-Difference (DID) model. Our results show that the UTC policy leads to an average decrease of 20.86% in women's employment income. Moreover, we reveal the mediation effect in the impact of the UTC policy on women's income and find that the UTC policy leads to a decrease in women's income by reducing their working hours and hourly wages. Furthermore, we find that the negative impacts of the UTC policy on women's employment income are greater among women under 35 years old and those without a bachelor's degree.